Clinical and Metabolic Signatures of FAM47E–SHROOM3 Haplotypes in a General Population Sample - Dariush Ghasemi-Semeskandeh; Eva König; Luisa Foco; Nikola Dordevic; Martin Gögele; Johannes Rainer; Markus Ralser; Dianne Acoba; Francisco S. Domingues; Dorien J.M. Peters; Peter P. Pramstaller; Cristian Pattaro (Kidney International Reports)
Introduction: Genome-wide association studies (GWAS) identified a locus on chromosome 4q21.1, spanning the Family With Sequence Similarity 47 Member E (FAM47E), Starch Binding Domain 1 (STBD1), Coiled-Coil Domain Containing 158 (CCDC158), and Shroom Family Member 3 (SHROOM3) genes, to be associated with kidney function markers. Functional studies implicated SHROOM3 as the effector gene, demonstrating its developmental role to guarantee podocyte barrier integrity. However, the locus has also been associated with other clinical traits, including electrolytes, hematological, cardiovascular, and neurological traits, not all of which can be easily traced to the regulation of kidney function. We therefore conducted a systematic analysis of the whole locus’ genetic profiles (haplotypes) to assess which phenotypic profiles they were associated with. Methods: For the 4 genes, we reconstructed haplotypes spanning 71 exonic and intronic variants for 12,834 participants in the Cooperative Health Research in South Tyrol (CHRIS) study based on genotypes imputed on a local whole-exome sequencing (WES) reference panel. Haplotypes were tested for associations with 72 clinical traits, 170 serum metabolites, and 148 plasma protein concentrations, using linear regression models. Results: We identified 11 haplotypes with a population frequency between 2% and 24%. Compared with the most common haplotype, most haplotypes were associated with higher creatinine-based estimated glomerular filtration rate (eGFR) and lower serum magnesium levels. In addition, specific haplotypes were also associated with biologically diverse groups of traits, including albuminuria, blood pressure, red blood cell traits, carnitines, and amino acids. Cluster analysis highlighted the existence of distinct genetic profiles in which individuals with specific haplotypes presented with specific phenotypic and metabolic signatures. Conclusion: The genetic variability of the FAM47E–SHROOM3 locus indicates the existence of population subgroups with distinct biomarker profiles.